Penggunaan Kaca Mata Koreksi pada Anak Usia Sekolah dengan Miopia terhadap Prestasi Belajar Di SDN Pacar Keling VI Surabaya - Dwi Susi Pristiwatin; Ika Yuni Widyawati; Erna Dwi Wahyuni (Universitas Airlangga, 2019)
Introduction: The aimed of using correctional glassesin school age children with miopiais to improve the eyesight so that disorder will not disturb the learning process in school. The aimed of this study was to describe correlation between the use of correctional glasses in school age children with miopiatoward learning achievement in SDN Pacar Keling VI Surabaya.Method: A cross sectional method was used in this study. The populations were school age children(at the age of 6-12 years) with miopiawho are using correctional glasses in SDN Pacar Keling VI Surabaya. Eighty four respondents were collected bysimple random sampling. Data were collected with direct observation, questionnaires and secondary grade report. Datawere analysis with “spearman rank” coefficient of statistic correlation, with significance level p0.05.Result: The results showed that there were correlation between the use of correctional glasses in school age children with miopia toward learning achievement with p=0,006 and r=0.297, there is indicated there was a low correlation between the use of correctional glasses in school age children with miopia toward learning achievement in SDN Pacar Keling VI Surabaya.Discussion: The conclusion of this research is using of correctional glasses could affect to sharpness of the eyesight. Good sharpness of the eyesight is very important for process of learning in the classroom. The school age children who are suffering miopia are suggested to wear correctional glasses during the process of learning and teaching in the classroom and also during learning by reading at their home, in order to avoid any missed-perception of their knowledge which could impact to their learning achievement.